Treatment With a Soluble Bone Morphogenetic Protein Type 1A Receptor (BMPR1A) Fusion Protein Increases Bone Mass and Bone Formation in Mice Subjected to Hindlimb Unloading. (9th October 2017) - Ko, Frank C.; Van Vliet, Miranda; Ellman, Rachel; Grasso, Daniel; Brooks, Daniel J; Spatz, Jordan M; Conlon, Chrissy; Aguirre, J Ignacio; Wronski, Thomas J; Bouxsein, Mary L
ABSTRACT: Previous work has shown that the soluble murine BMPR1A–fusion protein (mBMPR1A‐mFc) binds to BMP2 and BMP4 with high affinity, preventing downstream signaling. Further, treatment of intact and ovariectomized mice with mBMPR1A‐mFc leads to increased bone mass, and improved bone microarchitecture and strength, via increased bone formation and reduced resorption. In this study, we tested the effects of mBMPR1A‐mFc on disuse‐induced bone loss caused by 21 days of hindlimb unloading (HLU) via tail suspension versus cage controls (CONs). Adult female C57BL/6J mice (12 weeks old) were assigned to one of four groups ( n  = 10 each): CON‐VEH; CON‐mBMPR1A‐mFc; HLU‐VEH; and HLU‐mBMPR1A‐mFc. Mice were injected subcutaneously with VEH or mBMPR1A‐mFc (4.5 mg/kg, 2×/week). Leg BMD declined in the HLU‐VEH group (–5.3% ± 1.3%), whereas it was unchanged in HLU‐mBMPR1A‐mFc (–0.3% ± 0.9%, p  < 0.05 versus HLU‐VEH). Leg BMD increased significantly more in CON‐mBMPR1A‐mFc than CON‐VEH (10.2% ± 0.6% versus 4.4% ± 0.8%). In the femur, trabecular, and cortical bone microarchitecture was worse in the HLU‐VEH compared to CON‐VEH mice, whereas mBMPR1A‐mFc treatment for 3 weeks led to greater Tb.BV/TV, Tb.Th, and midshaft Ct.Th in both the HLU and CON groups compared to comparable VEH‐treated counterparts ( p  < 0.05). HLU‐mBMPR1A‐mFc mice also had 21% greater failure load ( p  < 0.05) compared to their VEH‐treated counterparts. Dynamic histomorphometry indicated that treatment with mBMPR1A‐mFc led to significantly greater mineralizing surface and mineral apposition rate, resulting in a 3.5‐fold and fivefold higher bone formation rate in the mBMPR1A‐mFc‐treated CON and HLU animals versus VEH groups, respectively. mBMPR1A‐mFc‐treated mice had a similar osteoblast surface but significantly lower osteoclast surface than VEH‐treated animals in both the CON and HLU groups. Altogether, these findings suggest that treatment with the soluble BMPR1A fusion protein may be useful for maintenance of skeletal integrity in the setting of disuse‐induced bone loss. © 2017 The Authors JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.